A Local Fractional Integral Inequality on Fractal Space Analogous to Anderson’s Inequality - Wei Wei; H. M. Srivastava; Yunyi Zhang; Lei Wang; Peiyi Shen; Jing Zhang (Abstract and Applied Analysis)
Anderson's inequality (Anderson, 1958) as well as its improved version given by Fink (2003) is known to provide interesting examples of integral inequalities. In this paper, we establish local fractional integral analogue of Anderson's inequality on fractal space under some suitable conditions. Moreover, we also show that the local fractional integral inequality on fractal space, which we have proved in this paper, is a new generalization of the classical Anderson's inequality.